Timeliness of malaria surveillance system in iran. - Hossein Akbari; Reza Majdzadeh; Abbas Rahimi Foroushani; Ahmad Raeisi (Tehran University of Medical Sciences, 2013)
We aimed to evaluate the timeliness of reporting of malaria surveillance system and understanding the existing problems.The timeliness of malaria surveillance system of Iran was evaluated in four provinces of Iran including Sistan & Baluchistan, Hormozgan, Kerman (as provinces with local malaria transmission) and Khuzestan (without local malaria transmission). In this descriptive-analytic cross-sectional study two levels of Primary Health Care service providers including first level (Health Houses) and second level (Urban or Rural Health care units) were evaluated with regard to reporting of malaria surveillance system.Forms number 1 (87% reported within one day) and number 2 (reporting median: 2 days) are reported from first level to second level, and forms number 4 (median: 4 days), number 3 (median: 6 days), number 7 (median: 9 days), number 5 (median: 11 days) and number 6 (median: 19 days) are reported from second level to the third level respectively in a shorter time. Independent variables such as distance, local malaria transmission level, and case finding type, are the factors affecting the reporting delay.Reporting in the first level compared to the second level is done with lower delay. In the areas where there is a deadline set for reporting, reporting is done more timely. Whatever number of malaria cases is decreased, sensitivity and subsequently timeliness reduced. It is recommended that the studies of timeliness be done with sensitivity and usefulness analysis of surveillance system.